Muslim Western Scholarship of Hadith and Western Scholar Reaction: A Study on Fuat Sezgin’s Approach to Hadith Scholarship - Kamaruddin Amin (Al-Jami'ah: Journal of Islamic Studies, 2008)
The following article is analyzing both Fuat Sezgin’s approach to Western scholarship of hadith and the views of some non-muslim scholars, which give either support or criticism against him. Some questions have been discussed; to what extent is Fuat Sezgin influenced by Western methods of hadith research and to what extent does he argue against the methods of non-Muslims? To what extent does he persist on arguing the reliability of hadith literature? To what extent does he base his argument on muslim hadith literature? To what extent does he digress from the classical methodology of hadith research? The following pages show that Sezgin has been familiar with non-Muslim scholarship of hadith research. Yet instead of following Western scholars’ approaches and premises on the early hadith literature, he severely criticized them and decided to follow the mainstream of Muslim scholars’ belief in the historicity of hadith transmission and collection. Fuat Sezgin focused his criticism on Goldziher’s historical claims. If one classifies Western discourse of hadith literature, Sezgin and Azmi can be located in the same line for their similar approach and way of handling the early literature of Islam. Both Sezgin and Azmi have been involved in the discussion on the reliability of early Islamic transmission. However, in contrast to Muslim scholars, who generally believe that the process of hadith transmission during the first century was mainly oral, they insist on arguing that many hadiths were, in fact, recorded in writing from the earliest times.